Flowering and production of Palmer mango trees under organic compound and paclobutrazol application - Prates, Paola Junayra Lima; Toledo Pereira , Marlon Cristian; Oliveira de Jesus , Mariana; Pimenta , Samy; Araújo Xavier, Helisson Robert; Brito de Oliveira, Moacir (Comunicata Scientiae, 2024)
The objective of this work was to evaluate the effects of applications of humified organic compound rates combined with paclobutrazol (PBZ) rates on the flowering, production, and fruit quality of Palmer mango trees grown in two production seasons (Seasons 1 and 2). Two experiments were conducted in different production seasons and areas in Matias Cardoso, MG, Brazil. A randomized block experimental design with four replications was used, in a 4×2+1 factorial arrangement, consisted of 4 humidified organic compound rates (10, 15, 20, and 25 mL plant-1), 2 PBZ rates (0.7 and 0.85 g per meter of canopy diameter), and a control (application of PBZ at 0.85 g per meter of canopy diameter). Vegetative, physiological, reproductive, production, and post-harvest fruit quality characteristics were evaluated. The data were subjected to analysis of variance and regression or mean tests. The treatments had significant effects on some characteristics in Season 1. Plants treated with the organic compound combined with PBZ had higher chlorophyll contents than those in the control. The increase in the organic compound rate linearly increased the total number of flowers and number of male flowers per axillary panicle, but decreased soluble solids content. The application of the lowest PBZ rate resulted in higher soluble solids content and titratable acidity in mango fruits. The treatments did not affect the evaluated characteristics in Season 2. The application of humidified organic compound combined with paclobutrazol showed no benefits for the management of floral induction in Palmer mango trees.